Low temperature fired ceramic and electronic component
By controlling the proportion of alkaline earth metal oxides in the glass component after firing and optimizing the oxide composition of the ceramic crystal components, the problem of large dielectric loss of low-temperature firing ceramics is solved, and high dielectric constant and small dielectric loss are achieved The effect is suitable for high-frequency electronic components.
Patent Information
- Application Number
- CN202380050445.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-01
- Filing Date
- 2023-06-22
- Publication Date
- 2025-02-18
AI Technical Summary
The dielectric loss of existing low-temperature fired ceramics is large, mainly because the content of alkaline earth metal oxides in the glass components of the firing body is insufficient, and crystals containing alkaline earth metal oxides may be precipitated during the firing process, resulting in increased dielectric loss. big.
By controlling the proportion of alkaline earth metal oxides in the glass component after firing, it is ensured to be less than 10 mol%, and dielectric loss is reduced. Specific measures include adding B2O3, SiO2 and alkaline earth metal oxides, such as BaO, to glass ceramic materials, and optimizing the oxide composition of the ceramic crystal components during the firing process, such as increasing the proportion of Ba2Ti9O20.
It realizes the dielectric loss reduction of low-temperature firing ceramics, improves the dielectric constant and Q value, and is suitable for high-frequency electronic components.
Smart Images

Figure CN119486981A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to low temperature fired ceramics and electronic components. Background Art
[0002] As a ceramic material for a ceramic multilayer wiring board, a glass ceramic material (LTCC material) capable of being fired at a low temperature is known.
[0003] For example, Patent Document 1 discloses a glass composition for a low-temperature fired substrate having a basic composition of RO-Al2O3-B2O3-SiO2 (wherein RO is one or more selected from MgO, CaO, SrO, BaO, and ZnO), in which RO and Al2O3 are both in the range of 1 to 25 mol % and the mol % ratio of SiO2 / B2O3 is less than 1.3, and a glass ceramic containing an aggregate in the glass composition for a low-temperature fired substrate.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2004-26529 Summary of the invention
[0007] In order to reduce the dielectric loss of glass ceramics, it is necessary to reduce the content of alkali metal oxides and alkaline earth metal oxides in the glass of the fired body. However, in Patent Document 1, only RO is specified to be less than 25 mol% for the composition of the glass before firing, and the composition of the fired body is not specified, so it is not necessarily possible to reduce the dielectric loss.
[0008] According to Patent Document 1, one of the reasons why the dielectric loss is not sufficiently reduced is that crystals containing alkaline earth metal oxides may be precipitated from the glass during firing. In this case, the content of alkaline earth metal oxides contained in the fired glass becomes less than the content of alkaline earth metal oxides contained in the glass before firing.
[0009] Another reason is that the ceramics mixed with the glass before firing often contain alkaline earth metal oxides (such as Ba2Ti9O 20 ), but it may be dissolved in the glass during firing. In this case, the content of the alkaline earth metal oxide contained in the glass of the fired body becomes greater than the content of the alkaline earth metal oxide contained in the glass before firing.
[0010] From this, it is considered that in order to reduce the dielectric loss, it is necessary to specify the alkaline earth metal oxide contained in the glass component of the fired body.
[0011] Based on the above, an object of the present invention is to provide a low-temperature fired ceramic having a small dielectric loss.
[0012] The low-temperature fired ceramic of the present invention contains oxides of a fired glass component and a ceramic crystal component, wherein the fired glass component contains B2O3, SiO2 and alkaline earth metal oxides, and the proportion of the alkaline earth metal oxides contained in the fired glass component is less than 10 mol%.
[0013] The electronic component of the present invention contains the low-temperature fired ceramic of the present invention.
[0014] According to the present invention, a low-temperature fired ceramic having a small dielectric loss can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 This is a cross-sectional view schematically showing an example of a multilayer ceramic electronic component as the electronic component of the present invention.
[0016] Figure 2 Yes means Figure 1 Schematic cross-sectional view of a laminated green sheet (unfired state) produced in the manufacturing process of a laminated ceramic electronic component. DETAILED DESCRIPTION
[0017] The low temperature fired ceramic and electronic components of the present invention are described below. It should be noted that the present invention is not limited to the following configurations and can be appropriately changed within the scope of the gist of the present invention. In addition, the schemes formed by combining multiple preferred configurations described below are still the present invention.
[0018] The low-temperature fired ceramic of the present invention is a fired body obtained by firing a glass ceramic material that can be sintered at a firing temperature of 1000° C. or less, that is, a low-temperature co-fired ceramic (LTCC) material.
[0019] The low-temperature fired ceramics of the present invention contain oxides of a glass component and a ceramic crystal component after firing.
[0020] The fired glass component contains B2O3, SiO2 and alkaline earth metal oxides. The ratio of the alkaline earth metal oxides contained in the fired glass component is 10 mol% or less.
[0021] In the low-temperature fired ceramic of the present invention, the ratio of the alkaline earth metal oxide contained in the glass component after firing is set to a small ratio, so that the low-temperature fired ceramic with small dielectric loss can be obtained.
[0022] Among the components contained in the low-temperature fired ceramic, the dielectric loss of the glass component after firing is large, and the dielectric loss of the oxide of the ceramic crystal component is small. For the dielectric loss of the low-temperature fired ceramic, the dielectric loss of the glass component after firing is dominant, so it is important to reduce the dielectric loss of the glass component after firing. Therefore, by setting the proportion of the alkaline earth metal oxide contained in the glass component after firing to a small proportion, the dielectric loss of the low-temperature fired ceramic becomes small.
[0023] The alkaline earth metal oxides contained in the glass component before firing contained in the low temperature co-fired ceramic (LTCC) material are precipitated outside the glass by firing, thereby reducing the proportion of alkaline earth metal oxides contained in the glass component after firing. By firing, the alkaline earth metal oxides are precipitated outside the glass, thereby obtaining a low-temperature fired ceramic with low dielectric loss.
[0024] The ratio of the alkaline earth metal oxide contained in the glass component after firing is preferably 8.0 mol% or less, more preferably 6.0 mol% or less. In addition, the ratio of the alkaline earth metal oxide contained in the glass component after firing may be 0.1 mol% or more.
[0025] The proportion of alkaline earth metal oxides contained in the glass component after firing is obtained by the following operation: the powder XRD (X-ray diffraction measurement) of the low-temperature fired ceramic (fired body) is measured by reducing the scanning speed (0.2 deg / minute), and the composition of the glass component is obtained by analysis using full spectrum fitting.
[0026] In addition, when measuring from a sample of a commercially produced sintered body, the composition of the glass component can be determined by measuring the glass region determined by STEM and electron beam diffraction of the peeled sample using WDS (wavelength dispersive X-ray analysis). In addition, the existing crystal phase can be identified by electron beam diffraction.
[0027] Examples of the alkaline earth metal oxide contained in the glass component after firing include MgO, CaO, SrO, and BaO, and BaO is preferred.
[0028] Preferably, the glass component further contains TiO2 after firing.
[0029] If the glass component contains BaO and TiO2 after firing, the dielectric constant can be particularly improved and the dielectric loss can be reduced.
[0030] Preferably, the glass composition does not contain Al2O3 after firing.
[0031] In Patent Document 1, Al 2 O 3 is included as an essential component of the glass composition in addition to B 2 O 3 and SiO 2. When the glass composition is used as a glass ceramic material capable of low temperature firing, the glass composition is mixed with ceramics and fired.
[0032] In order to increase the dielectric constant of glass ceramics, it is preferred to use Ba2Ti9O 20 However, when glass contains Al2O3 as a component, Al2O3 and Ba2Ti9O 20 Such ceramics react and decompose and therefore cannot be used.
[0033] Based on this, it is preferred that the glass component does not contain Al2O3 after firing.
[0034] In addition, it is preferred that the glass component does not contain alkali metal oxides after firing. By not containing alkali metal oxides after firing, low-temperature fired ceramics with low dielectric loss can be produced. In the case where the glass component contains alkali metal oxides after firing, the proportion of alkali metal oxides contained in the glass component after firing is preferably 0.1 mol% or less.
[0035] In summary, after firing, the glass composition preferably contains B2O3, SiO2, BaO and TiO2, and does not contain other oxides.
[0036] The preferred ratios of B2O3, SiO2, BaO and TiO2 contained in the glass component after firing are as follows.
[0037] B2O3: 21 mol%~65 mol%
[0038] SiO2: 24 mol%~62 mol%
[0039] BaO: 0.1 mol%~10 mol%
[0040] TiO2: 0.1 mol%~10 mol%
[0041] As the oxide of the ceramic crystal component, it is preferred to contain Ba2Ti9O 20 By containing Ba2Ti9O 20 , a low-temperature fired ceramic with a high dielectric constant and a small temperature change of the dielectric constant can be obtained.
[0042] Ba2Ti9O contained in low temperature fired ceramics 20 The ratio is preferably 55% by weight or more, more preferably 60% by weight or more, further preferably 70% by weight or more, particularly preferably 80% by weight or more.
[0043] In addition, the oxide of the ceramic crystal component may contain Ba2Ti9O 20 , and also contains BaTi(BO3)2, BaTi5O 11 , at least one of Ba2TiSi2O8 and TiO2.
[0044] Among the oxides of the above-mentioned ceramic crystal components, the oxides of the ceramic crystal components other than TiO2 have the characteristic that the dielectric constant becomes higher as the temperature rises. On the other hand, TiO2 has the characteristic that the dielectric constant becomes lower as the temperature rises. Therefore, by adding a specified amount of TiO2 to the oxides of the ceramic crystal components other than TiO2, the characteristics of the low-temperature fired ceramic can be adjusted in the direction in which the dielectric constant does not change with respect to the temperature. Therefore, TiO2 can be used for temperature change adjustment of the characteristics of the low-temperature fired ceramic. TiO2 as an oxide of the ceramic crystal component can be distinguished from TiO2 contained in the glass component after firing.
[0045] BaTi(BO3)2, BaTi5O 11 The preferred ratios of Ba2TiSi2O8 and TiO2 are as follows.
[0046] BaTi(BO3)2: 0 wt% to 20 wt%
[0047] BaTi5O 11 : 0 wt% to 20 wt%
[0048] Ba2TiSi2O8: 0 wt% to 20 wt%
[0049] TiO2: 0.1 wt% to 20 wt%
[0050] The ratio of the glass component after firing and the oxide of the ceramic crystal component contained in the low-temperature fired ceramic is not particularly limited. The ratio of the glass component after firing contained in the low-temperature fired ceramic can be 2.0 wt% to 30.0 wt%, and the ratio of the oxide of the ceramic crystal component can be 70.0 wt% to 98.0 wt%.
[0051] The relative density of the low temperature fired ceramic is preferably 90% or more, more preferably 95% or more. The relative density refers to the value obtained by dividing the density measured by the Archimedean method by the true density. If the relative density is less than 90%, the insulation may be reduced. If the relative density is 95% or more, according to experience, the insulation does not decrease.
[0052] The relative dielectric constant of the low temperature fired ceramic is preferably 15 or more, and the Q value, which is the inverse of the dielectric loss, is preferably 1000 or more. The dielectric loss is preferably 0.001 or less.
[0053] The relative dielectric constant and dielectric loss of the low temperature fired ceramic can be measured as the relative dielectric constant and dielectric loss at 3 GHz by a perturbation method.
[0054] The electronic component of the present invention includes the low-temperature fired ceramic of the present invention.
[0055] Examples of the electronic component of the present invention include a laminate having a plurality of low-temperature fired ceramic layers composed of the low-temperature fired ceramic of the present invention, a laminated ceramic electronic component having a laminated ceramic substrate using the laminate, and a chip component mounted on the ceramic substrate.
[0056] Since the electronic component of the present invention includes the low-temperature fired ceramic layer composed of the low-temperature fired ceramic of the present invention, it has a high dielectric constant and a low dielectric loss.
[0057] A laminate including a plurality of low-temperature fired ceramic layers composed of the low-temperature fired ceramic of the present invention can be used, for example, for a ceramic multilayer substrate for communication or a laminated dielectric filter.
[0058] The electronic component of the present invention has a high dielectric constant, a small dielectric loss, and a high Q value, and is therefore particularly suitable as an electronic component used in the millimeter wave frequency band.
[0059] Figure 1 FIG. 1 is a cross-sectional view schematically showing an example of a multilayer ceramic electronic component as an electronic component of the present invention. Figure 1 As shown, the electronic component 2 has a plurality of stacked ( Figure 1 The laminate 1 is a laminated body 1 formed by firing ceramic layers 3 at low temperature (five layers in the example), and chip components 13 and 14 mounted on the laminate 1. The laminate 1 is also a laminated ceramic substrate.
[0060] The low-temperature fired ceramic layer 3 is a fired body composed of the low-temperature fired ceramic of the present invention. Therefore, the laminated body 1 formed by laminating a plurality of low-temperature fired ceramic layers 3, and the electronic component 2 having a laminated ceramic substrate using the laminated body 1 and chip components 13 and 14 mounted on the laminated ceramic substrate (laminated body 1) are all electronic components of the present invention. The compositions of the plurality of low-temperature fired ceramic layers 3 may be the same as each other or different from each other, but are preferably the same as each other.
[0061] The laminate 1 may further include a conductor layer. The conductor layer may constitute, for example, a passive element such as a capacitor or an inductor, or a connection wiring that is responsible for electrical connection between elements. Such a conductor layer includes, for example, Figure 1 The conductor layers 9, 10, 11 and the via-hole conductor layer 12 are shown.
[0062] The conductor layers 9, 10, 11 and the via conductor layer 12 preferably contain Ag or Cu as a main component. By using such a low-resistance metal, signal propagation delay caused by the high frequency of the electrical signal can be prevented. In addition, since the low-temperature fired ceramic layer 3 is a fired body obtained by firing a low-temperature co-fired ceramic (LTCC) material, it can be formed by co-firing with Ag and Cu.
[0063] That is, the electronic component of the present invention preferably has Cu wiring embedded therein, and preferably has Cu wiring embedded therein formed by co-firing a low temperature co-fired ceramic (LTCC) material and Cu.
[0064] The conductor layer 9 is arranged inside the laminated body 1 . Specifically, the conductor layer 9 is arranged at the interface between the low-temperature fired ceramic layers 3 .
[0065] The conductor layer 10 is arranged on one main surface of the laminate 1 .
[0066] The conductor layer 11 is arranged on the other main surface of the laminate 1 .
[0067] The via hole conductor layer 12 is arranged to penetrate the low-temperature fired ceramic layer 3 , and plays a role in electrically connecting the conductor layers 9 of each layer, electrically connecting the conductor layers 9 and 10 , or electrically connecting the conductor layers 9 and 11 .
[0068] The laminated body 1 is produced, for example, as follows.
[0069] (A) Preparation of glass composition
[0070] The glass composition is prepared by mixing B2O3, SiO2 and alkaline earth metal oxide in a specified ratio. As the alkaline earth metal oxide, BaO is preferably used, and TiO2 is preferably added to the glass composition.
[0071] (B) Preparation of glass powder
[0072] The glass composition is melted, and the obtained melt is quenched to produce cullet. The cullet is coarsely pulverized and further pulverized using a ball mill or the like to produce glass powder having a predetermined particle size.
[0073] (C) Preparation of Low Temperature Co-fired Ceramic (LTCC) Materials
[0074] The low temperature co-fired ceramic material is prepared by mixing glass powder and an oxide of a ceramic crystal component. As the oxide of the ceramic crystal component, Ba2Ti9O 20 .
[0075] The ratio of the glass powder in the low temperature co-fired ceramic (LTCC) material is preferably 20 wt % to 40 wt %.
[0076] (D) Preparation of green sheets
[0077] A low temperature co-fired ceramic material is mixed with a binder, a plasticizer, etc. to prepare a ceramic slurry, and then the ceramic slurry is molded on a substrate film (eg, a polyethylene terephthalate (PET) film) and dried to produce a green sheet.
[0078] (E) Preparation of Laminated Green Sheets
[0079] The green sheets are stacked to produce a stacked green sheet (unfired state). Figure 2 Yes means Figure 1 Schematic diagram of the cross section of a laminated green sheet (unfired state) produced in the manufacturing process of a laminated ceramic electronic component. Figure 2 As shown, the laminated green sheet 21 is a laminated green sheet having a plurality of ( Figure 2 The green sheets 22 are formed by stacking the green sheets 21 (five sheets in the figure). The green sheets 22 become the low-temperature fired ceramic layers 3 after firing. The conductor layers including the conductor layers 9, 10, 11 and the via conductor layer 12 can be formed in the stacked green sheets 21. The conductor layers can be formed by screen printing, photolithography, etc. using a conductive paste containing Ag or Cu.
[0080] (F) Firing of Laminated Green Sheets
[0081] The laminated green sheet 21 is fired. As a result, the following Figure 1 The laminate 1 is shown.
[0082] The firing temperature of the stacked green sheets 21 is not particularly limited as long as it is a temperature at which the low-temperature co-fired ceramic material constituting the green sheets 22 can be sintered, and may be, for example, 1000° C. or lower.
[0083] The firing atmosphere of the laminated green sheet 21 is not particularly limited. When a material that is not easily oxidized, such as Ag, is used as the conductor layers 9, 10, 11 and the via conductor layer 12, an air atmosphere is preferred, and when a material that is easily oxidized, such as Cu, is used, a low-oxygen atmosphere such as a nitrogen atmosphere is preferred. Alternatively, the firing atmosphere of the laminated green sheet 21 may be a reducing atmosphere.
[0084] It should be noted that the laminated green sheet 21 can be fired in a state of being sandwiched by the constraining green sheet. The constraining green sheet contains an inorganic material (e.g., Al2O3) as a main component that is substantially not sintered at the sintering temperature of the low-temperature co-fired ceramic material constituting the green sheet 22. Therefore, the constraining green sheet acts in a manner that does not shrink during the firing of the laminated green sheet 21 and suppresses the shrinkage in the main surface direction of the laminated green sheet 21. As a result, the dimensional accuracy of the obtained laminated body 1 (particularly the conductor layers 9, 10, 11 and the via conductor layer 12) is improved.
[0085] The laminated body 1 can be mounted with the chip components 13 and 14 in a state of being electrically connected to the conductive layer 10. Thus, the electronic component 2 having the laminated body 1 is formed.
[0086] Examples of the chip components 13 and 14 include LC filters, capacitors, and inductors.
[0087] The electronic component 2 can be mounted on a mounting substrate (for example, a motherboard) so as to be electrically connected via the conductor layer 11 .
[0088] Example
[0089] Hereinafter, examples will be shown to more specifically disclose the low-temperature fired ceramic and electronic component of the present invention, but it should be noted that the present invention is not limited to these examples.
[0090] (A) Preparation of glass
[0091] Glass powders G1 to G4 (all in powder form) having the composition shown in Table 1 are prepared by the following method. First, glass raw material powders are mixed to obtain a glass composition. The glass composition is placed in a crucible made of Pt and melted at 1600°C for more than 30 minutes in an air atmosphere. Then, the obtained melt is quenched to produce cullet. It should be noted that carbonate (BaCO3) is used as a raw material for alkaline earth metal oxide (BaO). Carbonate (BaCO3) becomes alkaline earth metal oxide (BaO) by firing, and Table 1 shows the amount of compounding converted to BaO.
[0092] Then, the cullet was coarsely pulverized, put into a container together with ethanol and PSZ balls (diameter: 5 mm), and mixed using a ball mill. When mixing using the ball mill, the pulverization time was adjusted to obtain a glass powder with a median particle size of 1.0 μm. Here, the "median particle size" refers to the median particle size D50 measured by the laser diffraction scattering method.
[0093] (B) Preparation of Green Sheet
[0094] Next, glass powder and oxide of ceramic crystal components (median particle size 1.0 μm) were placed in ethanol and mixed using a ball mill according to the composition shown in Table 2, and a binder solution and a plasticizer dissolved in an organic solvent were mixed to prepare a slurry. The slurry was formed on a PET film with a doctor blade and dried at 40° C. to obtain a green sheet with a thickness of 50 μm.
[0095] The glass powder in the green sheet is mixed with Ba2Ti9O 20 The weight ratio of TiO2 is shown in Table 2 as "LTCC material before firing [wt%]".
[0096] (C) Preparation and evaluation of evaluation samples
[0097] As a sample for evaluating sinterability, the green sheet was cut into 50 mm × 50 mm and stacked 20 sheets, placed in a mold, and crimped using a punch. The crimped body was fired at 900 ° C in air for 60 minutes. After firing, the density was measured by the Archimedean method, and the relative dielectric constant and Q value (the inverse of dielectric loss) at 3 GHz were measured by the perturbation method. The measurement conditions are as follows.
[0098] [Measurement apparatus and measurement conditions]
[0099] Network analyzer: Keysight 8757D
[0100] Signal generator: Keysight Synthesized Sweeper 83751
[0101] Resonator: Homemade fixture (resonance frequency: 3GHz)
[0102] It should be noted that before the measurement, the network analyzer and the signal generator were connected to measure the cable loss. In addition, the resonator was calibrated using a standard substrate (quartz, relative dielectric constant: 3.73, Q value: 9091@3GHz, thickness: 0.636mm).
[0103] The fired body was pulverized and the true density of the powder was measured. The value obtained by dividing the density measured by the Archimedean method by the true density was defined as the relative density (%).
[0104] In order to further analyze the composition of the fired body, the powder XRD of the fired body was measured by reducing the scanning speed (0.2 deg / min), and the ratio of the glass component after firing contained in the fired body and the composition of the glass component after firing were obtained by analysis using full spectrum fitting. In order to obtain the composition, it was assumed that the total amount of oxides of each element before and after firing did not change.
[0105] In addition, the composition of the oxides of the ceramic crystal components contained in the fired body was also determined.
[0106] These results are shown in Tables 2 and 3.
[0107] [Table 1]
[0108]
[0109]
[0110] [Table 3]
[0111]
[0112] The ratio of alkaline earth metal oxides contained in the glass component after firing of the low-temperature fired ceramics of Sample Nos. S2, S3 and S5 (the ratio of BaO shown in Table 3) was 10 mol % or less, which corresponds to the low-temperature fired ceramics of the present invention.
[0113] All of these samples had high Q values, indicating that they were low-temperature fired ceramics with low dielectric loss. In addition, all of the samples had high relative dielectric constants.
[0114] In addition, the relative density was as high as 95% or more in all samples, so there was no decrease in insulation properties.
[0115] This specification discloses the following contents.
[0116] The present disclosure (1) is a low-temperature fired ceramic, comprising oxides of a glass component and a ceramic crystal component after firing, wherein the glass component after firing contains B2O3, SiO2 and alkaline earth metal oxides, and the proportion of the alkaline earth metal oxides contained in the glass component after firing is less than 10 mol%.
[0117] The present disclosure (2) is the low-temperature fired ceramics according to the present disclosure (1), wherein the alkaline earth metal oxide contained in the glass component after firing is BaO.
[0118] The present disclosure (3) is the low-temperature fired ceramics described in the present disclosure (1) or (2), wherein the glass component after firing further contains TiO2.
[0119] The present disclosure (4) is a low temperature fired ceramic in any combination with any one of the present disclosures (1) to (3), wherein the oxide of the ceramic crystal component contains Ba2Ti9O 20 .
[0120] The present disclosure (5) is the low temperature fired ceramic described in the present disclosure (4), wherein the Ba2Ti9O 20 The ratio is 55% by weight or more.
[0121] The present disclosure (6) is the low temperature fired ceramics as described in the present disclosure (4) or (5), wherein the oxide of the ceramic crystal component further contains BaTi(BO3)2, BaTi5O 11 , at least one of Ba2TiSi2O8 and TiO2.
[0122] The present disclosure (7) is an electronic component comprising the low-temperature fired ceramic in any combination with any one of the present disclosures (1) to (6).
[0123] The present disclosure (8) is the electronic component described in the present disclosure (7), wherein Cu wiring is built in.
[0124] Explanation of symbols
[0125] 1 Laminated body
[0126] 2 Electronic components
[0127] 3 Low temperature fired ceramic layer
[0128] 9, 10, 11 Conductor layer
[0129] 12 Via conductor layer
[0130] 13, 14 Chip components
[0131] 21. Laminated Green Sheets
[0132] 22 Green Sheet
Claims
1. A low temperature fired ceramic comprising: a glass component after firing, and an oxide of a ceramic crystal component, wherein: The fired glass component contains B2O3, SiO2 and alkaline earth metal oxides, and the ratio of the alkaline earth metal oxides contained in the fired glass component is less than 10 mol%.
2. The low temperature fired ceramic according to claim 1, wherein: The alkaline earth metal oxide contained in the fired glass component is BaO.
3. The low temperature fired ceramic according to claim 1 or 2, wherein: The fired glass composition also contains TiO2.
4. The low-temperature fired ceramic according to any one of claims 1 to 3, wherein The oxide of the ceramic crystal component contains Ba2Ti9O 20 .
5. The low temperature fired ceramic according to claim 4, wherein: The low temperature fired ceramic contains Ba2Ti9O 20 The ratio is 55% by weight or more.
6. The low temperature fired ceramic according to claim 4 or 5, wherein: The oxide of the ceramic crystal component also contains BaTi(BO3)2, BaTi5O 11 , at least one of Ba2TiSi2O8 and TiO2. 7 . An electronic component comprising the low-temperature fired ceramic according to claim 1 .
8. The electronic component according to claim 7, wherein Cu wiring is built in.
Citation Information
Patent Citations
Glass composition for low-temperature fired substrate and glass ceramics using the same
JP2004026529A